Copper supported on activated carbon from hydrochar of pomelo peel for efficient H2S removal at room temperature: Role of copper valance, humidity and oxygen. (1st July 2022) - Wang, Zhenqi; Huang, Jingchun; Zhong, Yi; Hu, Wei; Xie, Di; Zhao, Changxi; Qiao, Yu
Highlights: Porous activated carbon was obtained by KOH activation of pomelo peel hydrochar. Cu 0 -loaded activated carbon has higher removal capacity than other copper species. The desulfurization process involves catalytic oxidation and reactive adsorption. Removal capacity under moist condition is higher than oxygen or nitrogen condition. The terminated formation of sulphide and sulfate were earlier than elemental S. Abstract: In this work, the activated carbon prepared from KOH activation of pomelo peel hydrochar was selected as support to synthesize various valance copper adsorbents (maintaining a 20 wt% total content of copper) for H2 S adsorption at room temperature, with a focus on the desulfurization performance under moist or oxygen conditions. The results showed that Cu 0 /activated carbon has a highest H2 S breakthrough capacity of 358.3 mg/g under co-presence of steam and oxygen, followed by Cu + and Cu 2+ loaded activated carbon. The H2 S removal process consists of catalytic oxidation and reactive adsorption, resulting in the formation of large amount of elemental sulfur and part of sulfate and sulfide. The presence of steam or oxygen mainly enhances the catalytic oxidation of H2 S to form elemental sulfur, and the breakthrough sulfur capacity decreases in the order of moist oxygen, moist nitrogen, dry oxygen and dry nitrogen conditions. The evolution of desulfurization product at different reaction times indicate that the sulfate and sulfide are mainly generated at prometaphase stage of desulfurization, while the elemental sulfur could be formed in the whole stage. These findings provide a new route to prepare in-expensive and high efficient copper-based H2 S adsorbent from high moisture organic waste.